Pengaruh Empati Terhadap Perilaku Prososial Peserta Didik Sekolah Dasar - Yuli Mulyawati; Arita Marini; Maratun Nafiah (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2022)
This research is a quantitative research using a causal study. The purpose of the study was to determine the effect of empathy on prosocial behavior of elementary school students. The type of research is causal study. Data collection techniques by conducting documentation studies, interviews, observations and distributing questionnaires (surveys). The data processing was carried out in the form of testing the validity of the empathy instrument on students' prosocial behavior with the Pearson Product Moment formula and reliability testing with the Cronbach Alpha formula. The sample used in this study was 42 students, these results were obtained by the Taro Yamane formula. The price of the regression equation coefficient = 61.06 + 0.23x. This means that each increase of one unit of empathy variable will cause an increase of 0.23 units. The contribution of empathy to students' prosocial behavior is indicated by a correlation coefficient (rxy) of 0.93 with a determination of 86.49%. Based on the results of the study, it was concluded that there was an effect of empathy on the prosocial behavior of grade 3 students at SDN Cilendek 01 Bogor City in the 2021/2022 academic year. So, to improve students' prosocial behavior, one of them is by improving the empathy of their students.